Interdisciplinary Research Methods: Considering the Potential of Community-based Participatory Research in Translation - Bowker, Lynne (Université d'Ottawa | University of Ottawa, 2021)
Different disciplines have different research traditions, including the use of discipline-specific research methods. However, adopting methods from other disciplines can provide fresh perspectives and lead to new insights. Community-based participatory research (CBPR) originated in the population and public health field, but it has potential to be applied in a broader range of disciplines. This article explains the fundamental characteristics of CBPR, explores some misconceptions associated with this method, and describes some potential barriers to its application. Finally, using the example of a machine translation literacy project, the article walks readers through this example of how CBPR was applied to a translation-related research project and evaluates the success of this method for the project.
Keywords: ction research; community; interdisciplinarity; machine translation literacy; participatory research